Den komplexa väven Att organisera för barns övergångar till och från förskoleklass - Helena Ackesjö (Nordisk Barnehageforskning, 2015)
This study focuses on how children's transitions to and from preschool classes are organized in different schools. Principal’s arguments for this organization were sought via a web-based survey and analyzed using the frame factor theory in addition to theories of practical sense and the concept of continuity. The results show that children tend to make more transitions between social communities the younger they are. The distribution of the principal’s answers show that the majority of them, because of external conditions, split the preschool groups to new classes in the transition to preschool class. However, the same movements are not indicated in the transition to first grade. The results show how the work of organizing chidren’s transitions represent a complex web of external actual conditions as the number of children and the recruitment area of the school, the internal logics and ideas about what is best for children and best for continued learning as well as the school's own traditions of working with transitions.